Isolation and identification of acetoin-producing strain and its effect on solid-state multi-microbial fermentation products - CHEN Yuanyuan, CHEN Deming, LI Zijian, HUANG Dan, LUO Huibo (Zhongguo niangzao)
Acetoin (ACT) is a key precursor of tetramethylpyrazine (TTMP), an important functional substance in Baijiu. Acetoin-producing strains were screened and isolated from sauce-flavor Daqu, identified by morphological observation and molecular biology techniques, and applied to solid-state multi-microbial fermentation to investigate their effects on physicochemical indexes, organic acids, and volatile flavor compounds of fermentation products. The results showed that an acetoin-producing strain A12F_C118 was isolated and screened, and identified as Bacillus sonorensis. The moisture reducing sugar, total acid contents, and pH of the multi-microbial fermentation products with strain A12F_C118 addition increased by 39.40%, 38.46%, 127.63%, and 11.93%, respectively compared with the blank group. A total of 51 volatile flavor compounds were detected in the multi-microbial fermentation products with strain A12F_C118 addition, among them, the contents of important flavor compounds such as 1-pentanol, ethyl phenylacetate, ethyl caproate, tetramethylpyrazine, 2,5-dimethylpyrazine and trimethylpyrazine increased. Strain A12F_C118 could promote the synthesis of oxalic acid, L-malic acid, L-lactic acid, acetic acid and citric acid during solid-state multi-microbial fermentation, but its effect on succinic acid was not significant.